Validity of self reported diagnoses of cancer in a major Spanish prospective cohort study. Issue 7 (21st June 2006) - Navarro, C; Chirlaque, M D; Tormo, M J; Pérez-Flores, D; Rodríguez-Barranco, M; Sánchez-Villegas, A; Agudo, A; Pera, G; Amiano, P; Dorronsoro, M; Larrañaga, N; Quirós, J R; et al.
Abstract : Introduction: This study aims to assess the validity of self reported diagnoses of cancer by persons recruited for the Spanish EPIC (European prospective investigation into cancer and nutrition) cohort study and to identify variables associated with correctly reporting a diagnosis of cancer. Methods: 41 440 members of EPIC were asked at the time of recruitment whether they had been diagnosed with cancer and the year of diagnosis and site. The process of validating self reported diagnoses of cancer included comparison of the cohort database with the data from the population based cancer registries. Cancer diagnostic validity tests were calculated. The association between a correct report and certain sociodemographic, tumour related, or health related variables were analysed by logistic regression. Results: The overall sensitivity of self reported diagnoses of cancer is low (57.5%; 95% CI: 51.9 to 63.0), the highest values being shown by persons with a higher level of education or with a family history of cancer and the lowest values by smokers. Breast and thyroid cancers are those with the highest diagnostic validity and uterus, bladder, and colon-rectum those with the lowest. In both sexes the variables showing a significant association with a correct report of cancer are: higher education level, number of previous pathologies, invasive tumour, and, in women, a history of gynaecological surgery. Conclusions: The overall sensitivity of self reported diagnoses of cancer is comparatively low and it is not recommended in epidemiological studies for identifying tumours. However, self reported diagnoses might be highly valid for certain tumour sites, malignant behaviour, and average to high levels of education.